The Corinthian Correspondence: Redaction, Rhetoric, and History. By Frank W. Hughes and Robert Jewett - Esler, Philip Francis (The journal of theological studies, 2023)
There is a long-standing and widely held view in New Testament scholarship that 2 Corinthians is a composite of letter fragments, estimates of the number of such fragments varying from two to nine. In this book—the result of a friendship and conversation about the Corinthian correspondence between Frank Hughes and Robert Jewett going back to 1982—the authors accept this view and build on it to argue that 1 Corinthians is also such a composite. They further propose that what we have as canonical 1 and 2 Corinthians is an integrated combination of eight Pauline epistles to Corinth produced between 90 and 110 ce in pioneering codex form ‘in the struggle against early heresy among Jesus-believers’ that ‘required publication in redacted form that would replace the most dangerous Pauline letters that were being employed by teachers perceived to be heretics’ (p. 259). By bringing 1 Corinthians into the discussion so thoroughly, the authors probably represent the high-water mark in the application of partition theories to the Corinthian correspondence.